Preparation Method of Similar Materials for the Progressive Disintegration of Red-Bedded Soft Rock Based on Diagenesis Simulation - Xiaoming Liu; Dongcheng Jiang; Qinji Jia; Haifeng Xu; Tong Wang (Buildings, 2023)
Solid waste formed during the excavation of soft red stratum rock is often encountered in engineering practice. However, its reuse has been limited because it often shows a gradual degradation mechanism during water–rock interactions. Similarity simulation experiments of geotechnical materials have been developed to be environmentally friendly; however, their application in soft rock mechanics is still limited. Based on these limitations, this study aims to prepare red-bedded soft rock-like materials by referring to the diagenetic process of sedimentary rocks using low-melting-point glass powder (STGP) and high-temperature and vertical stress to accurately simulate the progressive disintegration properties of red-bedded soft rock. For this purpose, a series of laboratory tests were conducted to verify the function of STGP in the embedment of skeleton particles of soft rock as a cement material for resisting the dry–wet cycle. Micro-scanning electron microscopy, disintegration experiments with dry–wet cycles, and basic physical and mechanical property tests were conducted for the synthetic red soft rock-like material. Finally, the synthetic and natural materials were compared based on their density, microstructure, disintegration breakage, and uniaxial compression mechanical properties. The results showed that adding STGP promoted embedded solidification between aggregate particles. The simulated material exhibited the same characteristics of gradual disintegration breakage as natural red-bedded soft rock. Meanwhile, the basic physical and mechanical properties were in substantial agreement when the STGP content was 0.5~2%.